ASSESMENT FOR PROFESSIONAL FOOTBALL PLAYERS TO AVOID INJURIES, USING HUBER® 360 - Dorin Alexandru MUREȘAN; Mariana ARGHIR; Sergiu-Corneliu GAFENCU; Emilia Florina GROSU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2022)
The motor behavior of six football players aged 21 to 25 is investigated in this research. We examined the players using the HUBER® 360 platform and several functional tests such as the Stability test, Unipodal test, Stability limit test, Mobility restrictions test, and Upper and lower limb coordination test to obtain the information needed to avoid injuries while participating in performance sports. This study is relevant to footballers because injuries have a short-term detrimental impact on the health of the enhancers if they are discovered in time and a long-term negative impact if they are not detected. The preliminary testing on the HUBER® 360 equipment is specialized in defining the performance capacities of footballers and not only, by recognizing specific characteristics of the athletes, it is possible to correct them and thus improve sports performances. The data taken on such a group of football players are significant to the sport practiced as a professional, and so can be used to develop training methods and techniques for the sportsmen in question. Among those researched, it is discovered that corrective training sessions must be utilized, but it is also possible to specify which directions, positions, and speeds of movement must be avoided or used with caution.